IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA KURIKULUM MERDEKA DI SMAN 1 DRAMAGA BOGOR - ABDUL JABAR IDHARUDIN; WARTONO WARTONO; AGUS SARIFUDIN (ABDUSSALAM: Jurnal Pendidikan Dan Kebudayaan Islam, 2025)
The phenomenon of changing ministers leading to changes in the curriculum, as we are currently witnessing with the transition from the 2013 curriculum to the Merdeka curriculum, highlights the importance of conducting research on curriculum changes in Islamic Education (PAI) learning. This study uses a qualitative method to collect data through observation, interviews, and documentation, and analyzes the data through descriptive interpretive analysis. The research was conducted at SMAN 1 Dramaga Bogor. The results show that the implementation of PAI learning under the Merdeka curriculum at SMAN 1 Dramaga Bogor has been successfully realized, improving the quality of PAI learning in accordance with student needs and the evolving times. This success is driven by the commitment to quality teaching, supported by the school principal and other stakeholders. PAI learning is applied with a focus on innovation in managing lessons, evaluation that measures students' abilities holistically, and optimizing learning time through the integration of Islamic values in daily life, the development of integrated teaching materials, and the efficient use of technology.